The role of interleukin 33 in intestinal homeostasis - Chomka, A (2016)
IL-33 is a pleiotropic cytokine that orchestrates both innate and adaptive immunity. It is commonly associated with type 2 immune responses but recently expression of the IL-33 receptor, ST2, was reported on Treg cells found preferentially in non-lymphoid tissues, such as the visceral adipose tissue, muscle or colon. A crucial role of Tregs in maintaining intestinal homeostasis has been well described. However, little is known about the functional relevance of the ST2-expressing Treg population in the colon. Phenotypic and functional characterisation of Tregs in the gut revealed the presence of two distinct populations: ST2+/Gata3+ and Rorγt+ Tregs. Thymic-derived ST2+/Gata3+ Tregs showed a more activated phenotype and produced IL-10 under homeostatic conditions. Upon microbial challenge and colitis, ST2+/Gata3+ Tregs were decreased, while Rorγt+ Tregs expanded. Furthermore, in vitro experiments demonstrated that IL-33 directly induced activation of the Gata3 pathway in Tregs, which enhanced expression of Foxp3 and ST2. Additionally, amphiregulin was also induced in Tregs upon stimulation with IL-33. However, in vivo, IL-33 was dispensable for both the maintenance of Treg cells under homeostatic conditions and Treg function in Helicobacter hepaticus−driven colitis. Investigation of the negative regulators of IL-33 showed that IL-23 inhibited IL-33-mediated effects on Tregs. We also observed increased production of soluble ST2 by stromal cells during intestinal inflammation, which likely contributed to the reduction of IL-33 bioavailability. Finally, a systematic analysis of the cellular source of IL-33 revealed that PDGRFα+ stromal cells located in the T cell zone of secondary and tertiary lymphoid tissues were a major IL-33-producing cell population in the gut. Collectively, our findings suggest that signals received by the stromal compartment upon cell injury may trigger a specific phenotype of Tregs with a repair capacity, and thus, promote intestinal homeostasis. These findings improve our understanding of tissue-resident Tregs and open an exciting avenue to explore heterocellular signalling between stromal cells and Tregs.